The The GASING Method Based on Contextual Teaching and Learning in Improving Elementary Students’ Counting Automaticity - Rani Tartillah; Yunus Abidin; Yusuf Tri Herlambang (MIMBAR PGSD Undiksha, 2026)
Arithmetic automaticity is an important foundation in elementary mathematics because it enables students to access arithmetic facts quickly and accurately, allowing them to focus on conceptual understanding and problem-solving. However, this ability remains relatively low because mathematics learning tends to be mechanical and provides limited contextual and meaningful learning experiences.This study aims to analyze the effectiveness of implementing the GASING (Gampang, Asyik, dan Menyenangkan) method integrated with the Contextual Teaching and Learning approach in improving elementary students’ counting automaticity, as well as to examine its effectiveness across schools with different accreditation levels. The study employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 130 fourth-grade students from six elementary schools in Musi Banyuasin Regency, selected through purposive sampling. Research data were collected through the Mathematics Automaticity Test, classroom observations, and documentation, and were analyzed using N-Gain calculations, the Mann-Whitney test, and the Kruskal-Wallis test. The results indicate that learning through the GASING method integrated with Contextual Teaching and Learning produces significantly greater improvements in counting automaticity compared with conventional instruction and demonstrates consistent effectiveness across schools with different accreditation levels These findings indicate that integrating the GASING method and Contextual Teaching and Learning can effectively develop mathematical automaticity as a foundation for numeracy literacy and improve the quality of mathematics learning in elementary schools.